Three multi-responsive luminescent Zn-CPs for the detection of antibiotics/cations/anions in aqueous media. Issue 4 (23rd December 2022) - Fan, Chuanbin; Huang, Guimei; Xing, Zhiyong; Wang, Junli; Pang, Yaqin; Huang, Qingping; Huang, Shifu; Zong, Ziao; Guo, Feng
Abstract : The designed synthesized route of YMUN 6–8 . Abstract : Development of luminescent coordination polymers (LCPs) for effective detection of the environmental pollutants is urgent and important for human health and environmental protection. Three novel Zn-LCPs, {[Zn 1 (L)(4, 4′-bbibp)]–[Zn 2 (L)(4, 4′-bbibp)]} n [YMUN 6 (for Youjiang Medical University for Nationalities)], [Zn(L)(1, 4-bimb)] n (YMUN 7 ), and [Zn(L)(4, 4′-bidpe)] n (YMUN 8 ), were fabricated from flexible dicarboxylic acid 1, 3-bis(4′-carboxylphenoxy)benzene (H2 L) and different imidazole ligands [4, 4′-bbibp = 4, 4′-bis(benzimidazol-1-yl)biphenyl, 1, 4-bimb = 1, 4-bis(imidazol-1ylmethyl)benzene, 4, 4′-bidpe = 4, 4′-bis(imidazolyl)diphenyl ether] using solvothermal conditions. They were characterized using X-ray diffraction (XRD), infrared (IR), thermogravimetric (TG), powder X-ray diffraction (PXRD), and photoluminescence (PL) spectroscopic techniques. YMUN 6 possessed the "ABAB" interpenetrating 2D complanate structure. YMUN 7 showed a three-interpenetrating 2D network. YMUN 8 displayed a hcb 3-connected 3-fold interpenetrated 2D network. Photoluminescent properties of YMUN 6–8 were investigated, and 6–8 served as "turn off" sensors that could detect chlortetracycline (Chl ), Ag +, and Cr2 O7 2− in an aqueous solution with simultaneous high efficiency and sensitivity. Notably, the investigation of Ag + sensing was most focused on lanthanide metal LCPs, and Zn-LCPs have rarely been reported in this direction. Furthermore, selectivity and recyclability were also investigated.